Effect of soy and pea protein isolate addition on the physicochemical properties of mung bean protein-based burger patties - Ratnaningsih, Ratnaningsih; Songsermpong, Sirichai; Jittanit, Weerachet (Journal of Food Technology Research, 2026)
The incorporation of protein isolated from legumes, such as soy and pea protein isolates, into meat analogs has been reported to enhance their textures and overall quality. This study aims to examine the impact of including soy and pea protein isolates on the physicochemical properties of mung bean protein-based burger patties. Nine combination treatments were used in this study: MBP (4,0), MBP-SP (3:1), MBP-SP (2:2), MBP-SP (1:3), SP (0:4), MBP-PP (3:1), MBP-PP (2:2), MBP-PP (1:3), and PP (0:4). The findings indicate that the addition of soy protein isolate alone or pea protein isolate alone increases the protein content of the patties up to 41% on a dry basis, along with enhancing mineral content, including calcium, magnesium, and zinc. The addition of soy protein isolates reduces the brightness of the patties, with values decreasing up to 40.74, whereas the integration of pea protein isolate maintains brightness at 51.17 and increases redness up to 15.27 and yellowness up to 11.19. The inclusion of soy and pea protein isolates reduces the hardness, with values reaching up to 0.91 kgf and 0.94 kgf, respectively, and decreases chewiness, with values up to 0.084 kgf and 0.171 kgf, respectively. Using pea protein isolates alone in burger patties made from mung bean protein results in enhanced coloration compared to soy protein isolates. Microstructure analysis indicates that patties with soy protein isolate exhibit a more consistent lipid distribution than those made with pea protein isolate.